Design and Fabrication of All Organic Field Effect Transistor - Suprapto Suprapto; Krishna C. Persaud (Jurnal Fisika dan Aplikasinya, 2011)
All organic field effect transistor consist of poly-3-hexyloxythiophene, undoped poly-3,3”-didecyl-2,2’,5’,2”-terthiophene and polypyrrole has been successfully developed. Poly-3-hexyloxythiophene was applied as gate material. Undoped poly-3,3”-didecyl-2,2’,5’,2”-terthiophene was used as insulating layer and polypyrrole was applied as source-drain material. The multilayer polymers were deposited onto gold source-drain and gate electrodes by electropolymerization method. The spaces between the gold electrodes were 50 μm. The transistor shows a current amplification upon increasing gate voltages. Good conductivity stability upon increasing gate voltages was observed. Overall the field effect transistor has properties that similar to inorganic field effect transistor.